DEVELOPMENT OF A COASTAL OCEAN ACIDIFICATION VULNERABILITY INDEX (COAVI) - Tajam, Jamil; Rosmee, Nurul Hidayah; Mohd Ishak, Mohd Azlan; Saleh, Sabiha Hanim; Tan, Aileen Shau Hwai; Mokhtar, Mazlin; Abd. Aziz, Khairul Naim; Kamaruddin, Sharir Aizat; Ismail, Md Nizam (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2025)
Coastal ocean acidification (COA), driven by rising atmospheric CO₂ levels and localized stressors such as eutrophication and freshwater inputs, poses significant risks to marine ecosystems, fisheries, and coastal communities. Despite its increasing impact, there is limited assessment of COA vulnerability at regional and local scales. This study proposes the development of a Coastal Ocean Acidification Vulnerability Index (COAVI) to systematically quantify and map the susceptibility of coastal environments. The COAVI integrates three key components: (i) Exposure, which includes coastal Total Alkalinity, pH variability, Sea Surface Temperature, Salinity, fCO2, Aragonite and Calcite Saturation State (ΩAr & ΩCal), (ii) Sensitivity, which considers the presence of calcifying species and calcification rates and (iii) Adaptive Capacity, which evaluates socioeconomic resilience, and mitigation strategies. Data will be collected from remote sensing sources, in-situ monitoring, scientific literature, and national reports, followed by normalization, weighting, and spatial analysis using Geographic Information System (GIS) tools. The resulting index will identify high-risk coastal regions, providing a valuable tool for policymakers, researchers, and conservationists to prioritize intervention strategies. By systematically assessing COA vulnerability, this study aims to support sustainable coastal management and enhance climate resilience in marine-dependent communities.